Dopamine-induced SULT1A3/4 promotes EMT and cancer stemness in hepatocellular carcinoma - Juan Zou; Hong Li; Qianling Huang; Xiaomin Liu; Xiaoxiao Qi; Ying Wang; Linlin Lu; Zhongqiu Liu (Tumor Biology, 2017)
Hepatocellular carcinoma has the second highest incidence rate among malignant cancers in China. Hepatocellular carcinoma development is complex because of the metabolism disequilibrium involving SULT1A3/4, a predominant sulfotransferase that metabolizes sulfonic xenobiotics and endogenous catecholamines. However, the correlation between SULT1A3/4 and hepatocellular carcinoma progression is unclear. By utilizing immunofluorescence and immunohistochemical analysis, we found that in nine hepatocellular carcinoma clinical specimens, SULT1A3/4 was abundantly expressed in tumor tissues compared to that in the adjacent tissues. Moreover, liver cancer cells (HepG2, MHCC97-L, and MHCC97-H) had higher basal expression of SULT1A3/4 than immortalized liver cells (L02 and Chang liver). Ultra-high-pressure liquid chromatography–tandem mass spectrometry assay results further revealed that the concentration of dopamine (a substrate of SULT1A3/4) was negatively correlated with SULT1A3/4 protein expression. As a transcriptional regulator of SULT1A3/4 in turn, dopamine was used to induce SULT1A3/4 in vitro. Interestingly, dopamine significantly induced SULT1A3/4 expression in liver cancer HepG2 cells, while decreased that in L02 cells. More importantly, the expression levels of epithelial–mesenchymal transition biomarkers (N-cadherin and vimentin) and cell stemness biomarkers (nanog, sox2, and oct3/4) considerably increased in HepG2 with dopamine-induced SULT1A3/4, whereas in L02, epithelial–mesenchymal transition and cancer stem cell–associated proteins were contrarily decreased. Furthermore, invasion and migration assays further revealed that dopamine-induced SULT1A3/4 dramatically stimulated the metastatic capacity of HepG2 cells. Our results implied that SULT1A3/4 exhibited bidirectional effect on tumor and normal hepatocytes and may thus provide a novel strategy for hepatocellular carcinoma clinical targeting. In addition, SULT1A3/4 re-expression could serve as a biomarker for hepatocellular carcinoma prognosis.